2006
DOI: 10.3892/or.15.1.267
|View full text |Cite
|
Sign up to set email alerts
|

High energy shock waves enhance the cytotoxic effect of doxorubicin and methotrexate to human osteosarcoma cell lines

Abstract: Abstract. Despite recent advances, the prognosis of relapsed osteosarcoma patients remains very poor. Application of high energy shock waves may change the tumour cell growth and increase the cytotoxic effect of in vivo and in vitro chemotherapeutic agents. We studied the effect of their association with doxorubicin or methotrexate on three in vitro osteosarcoma cell lines. The effect of these combinations on SJSA-1, MG-63 and HOS human osteosarcoma cell lines were evaluated through incubation with doxorubicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Furthermore, DOX treatment can decrease the number of human OS cells. However, the apoptotic effect of this treatment is not yet known, and the treatment can increase relative RNA expression of ZAK . To determine the effect of ZAKα and the DOX treatment on human OS cells, we treated human OS cells with DOX.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, DOX treatment can decrease the number of human OS cells. However, the apoptotic effect of this treatment is not yet known, and the treatment can increase relative RNA expression of ZAK . To determine the effect of ZAKα and the DOX treatment on human OS cells, we treated human OS cells with DOX.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of ZAKα overexpression in human OS cells is not yet known. Recently, it was shown that DOX could provide a statistically significant advantage in terms of a decrease in cell number and cell proliferation but not in an increase in apoptosis in human OS cell lines . Based on previous data, we have formed a hypothesis that the DOX treatment can induce ZAK overexpression with a subsequent decrease in cell proliferation and increase in apoptosis in human OS cells.…”
Section: Introductionmentioning
confidence: 91%
“…ESWs can be focused with high precision in depth, and they determine permeabilization of plasma membranes (Lauer et al 1997, Kodama et al 2002, Frairia et al 2003, Catalano et al 2007. As a consequence of ESWinduced cell permeability, ESWs increase the cytotoxic effects of different anti-cancer drugs (Frairia et al 2003, Palmero et al 2006, Catalano et al 2007, Canaparo et al 2008. All these features make ESWs an ideal tool to be used in combination with drug-loaded NBs.…”
Section: :6mentioning
confidence: 99%
“…Recent advances suggest that shock wave treatment may sensitize osteosarcoma cells to chemotherapeutic drugs [ 8 ]. Shock waves are elicited by a transient pressure disturbance and characterized by high positive pressure.…”
Section: Introductionmentioning
confidence: 99%